Interiors [videorecording (DVD)] - Allen, Woody, 1935-; Griffith, Kristin; Hurt, Mary Beth; Jordan, Richard, 1937-1993; Keaton, Diane; Marshall, E. G., 1914-1998; Page, Geraldine; Stapleton, Maureen; Waterston, Sam (MGM Home Entertainment, 2005)
When Eve, an interior designer, is deserted by her husband of many years, the emotionally glacial relationships of their three grown daughters are laid bare. Twisted by jealousy, insecurity and resentment, Renata, a successful writer; Flyn, a woman crippled by indecision; and Joey, a budding actress, struggle to communicate for the sake of their shattered mother.